REPRODUCTION AND HABITAT OF TEN BRAZILIAN FROGS (ANURA) - Giaretta, Ariovaldo A.; Facure, Katia G. (Contemporary Herpetology, 2008)
Basic data on habitat, behavior, and reproduction arelacking for most Neotropical frog species and even highertaxonomic groups (Crump 1974; Haddad and Prado2005), particularly for those restricted to the AtlanticForest. Basic reproductive features are the basis of comparativestudies on evolution of major natural historyfeatures (Harvey and Pagel 1998), such as the interspecific relationship between body size and egg number/size (Salthe and Duellman 1973, Crump 1974, Stearns1992). Here, we present data on habitat, reproductivebehavior and quantitative parameters such as adult sizes,egg numbers/sizes of ten sympatric frogs of an altitudinalAtlantic Forest site in Southeastern Brazil.